Treatment of impacted third molars in dento-alveolar surgery due to one year analysis records - Szabolcs Gyulai-Gaál; Fanni Minya (Hungarian Dental Association, 2019)
Wisdom teeth are the most commonly impacted teeth that can cause pathological lesions and orthodontic problems. In one year 1048 surgical wisdom teeth removal were performed in our department of which 700 cases were radiologically and statistically analyzed. 2/3 of the wisdom teeth were removed from the mandible and 1/3 from the maxilla. 21%, of teeth were completely and 31% partially erupted while 48% were fully impacted. The percentage of the therapeutic, preventive and orthodontic indications were almost equal. Pericoronitis and caries were the most common therapeutic indications for surgical extraction. Less common indications were periodontal pocket formation, focal infection, follicular cyst, root resorption of adjacent teeth, trismus and odontoma. The ideal age for preventive and orthodontic wisdom teeth removal is between 16 and 23 when less than 2/3 of the roots have formed. 20% of the removals in our department were performed within the above age range which demonstrates the spreading of our approach in everyday practice. During the radiological assessment the angulation and root formation of the wisdom teeth, depth of impaction, distance from the distal site of second molar to the ramus mandible and the relationship of the wisdom teeth to the canalis mandible were observed. Postoperative complications, such as prolonged swelling and pain, occurred only in 6% of the cases. There was only one wound dehiscence and one mandibular nerve damage among the total number of cases. Preoperative radiological assessment and CBCT examination in complicated cases are recommended to reduce postoperative complications.